Development and immunogenicity evaluation of a quadruple-gene-deleted pseudorabies virus strain - Li, Hui; Zhang, Riteng; Qu, Jiahao; Kang, Yahao; Zhang, Jingnan; Guo, Ruhai; Li, JunDa; Zhang, Xiao; Han, Likang; Xie, Honglin; Wang, Xinglong (Frontiers in Microbiology, 2024)
Since 2011, the emergence of Pseudorabies virus (PRV) variants has led to significant vaccine failures, resulting in severe economic losses in China’s swine industry. Conventional PRV vaccines have shown limited efficacy against these emergent variants, underscoring the urgent need for novel immunization strategies. This study aimed to develop and evaluate a novel recombinant PRV vaccine candidate with improved safety and immunogenicity profiles. Utilizing the homology-directed repair (HDR)-CRISPR/Cas9 system, we generated a recombinant PRV strain, designated PRV SX-10ΔgI/gE/TK/UL24, with deletions in the gI, gE, TK, and UL24 genes. In vitro analyses demonstrated that the recombinant virus exhibited similar replication kinetics and growth curves comparable to the parental strain. The immunological properties of the recombinant PRV were assessed in murine and porcine models. All animals inoculated with PRV SX-10ΔgI/gE/TK/UL24 survived without exhibiting significant clinical signs or pathological alterations. Immunological assays revealed that PRV SX-10ΔgI/gE/TK/UL24 elicited significantly higher levels of gB-specific antibodies, neutralizing antibodies, and cytokines (including IFN-γ, IL-2, and IL-4) compared to both the Bartha-K61 and PRV SX-10ΔgI/gE/TK strains. Notably, both murine and porcine subjects immunized with PRV SX-10ΔgI/gE/TK/UL24 demonstrated enhanced protection against challenges with the variant PRV SX-10 strain, compared to other vaccine strains. These findings suggest that PRV SX-10ΔgI/gE/TK/UL24 represents a promising PRV vaccine candidate strain, offering valuable insights for the prevention and control of PRV in clinical applications.